(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The Burhi Gandak river basin is bounded by the Himalayas in the north, Ganga River in the south, the Kosi River in the east, and the Great Gandak in the west. It originates from the Chautarwa Chaur Terai region near Bishambharpur, Bihar district of West Champaran. It is known in its upper reaches as Sikrana. Harha, which emerged near Someshwar Hill, collects water from several mountainous rivers and is known as Masan in the plain and is Sikrana’s primary source of water. A second mountainous flow, Singha, is divided into two, one joins Harha and Masan near Churharwa and one identified as Ramrekha joins Sikrana. Rivers Masan and Ramrekha join Lauria Nandangarh in creating Sikrana, which greatly contributes to its discharge. Dhanauti, a highly sinuous nearly deserted river, meets Sikrana near Pakridayal village, Motihari and after this confluence is renamed Burhi Gandak, the Sikrana.